Transesterificação de triglicerídeos de fonte vegetal e animal catalisada por preparações comerciais de lipase imobilizada na presença de etanol visando a produção de biodiesel - Tiosso, Poliana Carneiro (2010)
In this work we synthesized ethyl esters of babassu oil, Jatropha, palm, andiroba and tallow by enzymatic transesterification. Initially the physicochemical properties of the raw materials were determined, such as, as acidity, peroxide and iodine indices and fatty acid composition. Three different lipases were used for doing the transesterification reactions: lipase from Candida antartica (Novozym 435) immobilized on macroporous acrylic resin, lipase from Thermomyces lanuginosus (Lipozyme TL IM) immobilized on porous silica and granulated lipase from Burkholderia cepacia (Lipase PS) immobilized in diatomite. The reactions were conducted in a closed reactor containing 20 g of substrate, which consisted of oil or animal fat and anhydrous ethanol, without the presence of solvents in an oil-ethanol molar ratio of 1:9 for vegetable oils and 1:6 for tallow. The mixture was incubated with lipases from different sources under a loading of 10% w/w of enzyme and reaction mass of the medium. The experiments were performed at 50°C under magnetic stirring, for a maximum period of 48 hours. Samples were collected to quantify ethyl esters formed by gas chromatography. The kinematic viscosity of biodiesel produced was also measured. The highest yields were obtained by babassu oil and Jatropha, with enzymes Novozym 435 (94,90 and 98,85%) and Lipase PS (96,92 and 100%). Although only biodiesel made from babassu oil had reached in 48h viscosity in the range 3,0 to 6,0 cSt, as determined by the National Petroleum Agency for x the use of biofuels in the country, the enzymatic process was able to produce biodiesel with good quality.